BIOCHAR EFFECT AT POTASSIUM FERTILIZER AND DOSAGE LEACHING POTASSIUM FOR TWO-CORN PLANTING SEASON - Widowati, Widowati; Asnah, Asnah (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2014)
An experiment in greenhouse was conducted to study the effect of biochar and fertilizer potassium against leaching and uptake of potassium on the growth of maize during the two cropping seasons. In the experiment, a randomized block design with seven treatments and three-time replication was applied, namely control (without biochar and KCl), biochar (30 t ha-1) with various doses of potassium fertilizer (0, 50, 100, 150 and 200 kg KCl ha-1) and potassium fertilizer treatment of 200 kg KCl ha-1 without biochar. The first planting used 90 kg N ha-1 basic fertilizer and 100 kg P2O5 ha-1, while the second planting fertilizer was added with 90 kg N ha-1. The results showed that biochar containing potassium was soluble and leached. The amount of potassium leached from the soil given the biochar 30 t ha-1 did not differ from that given 200 kg KCl ha-1. The amount of potassium leached was not different, ranging from 439-449 mg l-1 in the first growing season (MT I) and 16-23 mg l-1 in the second growing season (MT II) at various doses of KCl with biochar.Keywords: biochar, leaching, potassium, uptake